Environmental Policies and Dirty Products: Do Pollution Havens Exist? Evidence from East Asia - , Soca Indriya, SE.; , Dr. Tri Widodo, Mec., Dev. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This paper aims to analyze indications of pollution havens in the East Asia and the trade patterns of dirty products in East Asia. This research using secondary data, 10 East Asian countries namely Japan, Malaysia, Indonesia, Macao, Hong Kong, Singapore, Thailand, China, Korea, and Philippines are sourced from the United Nations Commodity Trade Statistics Database (UN-COMTRADE). The analysis was performed with the Trade Balance Index to analyze the trade in dirty products, the unit root test to see stationery data to identify indications of pollution havens, Revealed Symmetric Comparative Advantage (RSCA) to see the indicator of comparative advantage, and linear regression to see the dynamics of comparative advantage. The research found that the weak indication of pollution havens. The existence of pollution havens but the trend is not significant, and the existence of comparative advantage in dirty products in East Asia.